Keep Fit for Life : Meeting the Nutritional Needs of Older Persons. - Organization, World Health (World Health Organization, 2002)
Given the impact that good nutrition and keeping fit have on health and well-being in later life, WHO, in collaboration with the Tufts University USDA Human Nutrition Research Center on Aging, organized a consultation to review the scientific evidence linking diet and other factors - especially exercise - affecting nutritional status, disease prevention and health promotion for older persons. The consultation focused primarily on practical issues, including the establishment of explicit recommendations to improve the health and nutritional status of older persons in a wide variety of socioecon.